Study On Prevelence Of Skin infections and Its Antibiogram In Canines In Visakhapatnam (Urban) - Mohinikumari Paidi; Himaja Maddireddy; Nagavalli Yelleti; Srikala Devarakonda (The Indian Veterinary Journal, 2025)
Skin scrapings and tape impression smears were collected from dogs of different age group, sex and season. All samples were subjected for isolation, identification and Antibiotic Sensitivity Test for etiological agent. A total of 664 samples were collected in Visakhapatnam city for a period of 3 years and analysed. A total of 218 samples were found positive for parasitic ( 71), yeast (68 ), bacterial infections (21) and  no concurrent infection